2012
DOI: 10.1186/1476-0711-11-34
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antiretroviral therapy (ART) during the early months of treatment in rural Zambia: influence of demographic characteristics and social surroundings of patients

Abstract: BackgroundAround 70% of those living with HIV in need of treatment accessed antiretroviral therapy (ART) in Zambia by 2009. However, sustaining high levels of adherence to ART is a challenge. This study aimed to identify the predictive factors associated with ART adherence during the early months of treatment in rural Zambia.MethodsThis is a field based observational longitudinal study in Mumbwa district, which is located 150 km west of Lusaka, the capital of Zambia. Treatment naive patients aged over 15 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 38 publications
7
48
4
Order By: Relevance
“…The adherence rate was better in our settings compared to some studies [18][19][20] ; however, other studies conducted elsewhere have shown higher adherence to ART compared to our study findings. 10,12,[21][22][23][24][25][26][27] Better adherence in our settings could be due to the fact that all PLHIV receive free ART, regular adherence monitoring, and better literacy rate and awareness about HIV disease in coastal South India.…”
Section: Discussioncontrasting
confidence: 89%
“…The adherence rate was better in our settings compared to some studies [18][19][20] ; however, other studies conducted elsewhere have shown higher adherence to ART compared to our study findings. 10,12,[21][22][23][24][25][26][27] Better adherence in our settings could be due to the fact that all PLHIV receive free ART, regular adherence monitoring, and better literacy rate and awareness about HIV disease in coastal South India.…”
Section: Discussioncontrasting
confidence: 89%
“…Other factors which were statistically insignificant in this study were; ethnicity, religion, marital status, level of education, living condition and source of support. Although in some studies association between marital status and adherence levels were also not established, in Zambia unmarried people were found more non-adherent [8,10,11]. Similarly, some studies did not yield any association between education level and adherence levels, but others have documented significance [8,10,12,13].…”
Section: Socio-demographic and Economic Characteristicsmentioning
confidence: 99%
“…Notably, the efficacy of any treatment depends on sustained high levels of adherence to ART. But ART regimens are often According to WHO, the interventions target adherences was tailored to the demands that experienced by the patients with that specific illness [7]. As a result, it is important for health care providers to assess those factors that impact negatively on adherence.…”
Section: Introduction Issn: 2454-499xmentioning
confidence: 99%
“…If there is poor adherence then there is a higher risk that drug resistance will develop, which will result in need for second-line drug treatment. When people living with HIV require second line treatment, it can be ten times more expensive than first line drugs [7].…”
Section: Introduction Issn: 2454-499xmentioning
confidence: 99%